2021
DOI: 10.3390/foods10020247
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Commercial Yeasts on Volatile Fraction of Sparkling Wines

Abstract: The occurrence of aroma constituents in sparkling wines, with direct impact on their organoleptic characteristics, is affected by several factors, for example the base-wine particularities, grapes cultivar conditions, inoculated yeasts, the aging stage, and wine-making practices. This study evaluated the influence of different four commercial yeasts (IOC FIZZ™, IOC DIVINE™, LEVULIA CRISTAL™, and IOC 18-2007™) on the volatile composition of experimental sparkling wines. For this, five sparkling wines variants f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…Previous studies [26][27][28] showed similar results on sparkling wines and are in accordance with other literature data [29].…”
Section: Physicochemical Characteristics Of Winessupporting
confidence: 92%
“…Previous studies [26][27][28] showed similar results on sparkling wines and are in accordance with other literature data [29].…”
Section: Physicochemical Characteristics Of Winessupporting
confidence: 92%
“…Sonication together with low pressure and temperature can be a method of pasteurising the juice. By pasteurization treatment, the colour of the juice is significantly affected, while heat, generates an important loss of volatile compounds [167]. This alternative pasteurization method consists of the application of high-intensity ultrasound (20-100 kHz and 10-1000 W/cm 2 ).…”
Section: Ultrasound Treatmentsmentioning
confidence: 99%
“…A recent paper by Cotea, Focea, Luchian, Colibaba, Scutaras , u, Marius, Zamfir and Popîrdă [6] showed that, despite the limited influence of five different commercial yeast strains on many physico-chemical parameters of sparkling wines, the impact on wine volatile compounds was statistically significant. By quantifying 20 volatile compounds and carrying out sensory analysis of the wines, the authors showed that some strains confer more floral odor notes, particularly elderflowers, while others, fruitier notes, e.g., green banana.…”
Section: Compoundmentioning
confidence: 99%
“…Wine aroma is strongly influenced by the yeast strain that conducts the fermentation [1][2][3][4]. Each strain has its own characteristics, different from those of the other strains, capable of influencing the gustatory and aromatic balance of the wine [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation